South Sudanese refugees in Uganda face overwhelming odds against COVID-19 - McKague, Kevin (South Sudan Medical Journal, 2020)
Life in Northern Uganda’s Kiryandongo refugee settlement is difficult at thebest of times. Nearly 60,000 refugees, who are predominantly South Sudanese, contend with overcrowding and limited access to healthcare services, especially mental health and psychosocial support.[2, 3] It is into this environment that the COVID-19 pandemic will soon be introduced. “Case numbers are increasing exponentially in the African region,” said Dr Matshidiso Moeti, the World Health Organization (WHO) regional director for Africa.[3] It took twenty-six days to reach one-thousand cases of COVID-19 in Africa. Five days later, the number of cases had tripled across the continent.[4] When this highly infectious respiratory disease arrives in Kiryandongo, the results may be devastating.Professor Pauline Byakika, a specialist in infectious diseases at Uganda’s Makerere University, says that fighting the virus in a refugee camp will come down to prevention and control.[5] The United Nations High Commissioner for Refugees (UNHCR) agrees. At Uganda’s border, the UN has established handwashing and temperature screening facilities. They are educating refugees already in Uganda about hygiene and sanitation while training health workers and increasing distribution of hygiene products.[6] Such measures may keep the daily number of cases at a low level. However, flattening the curve in a refugee settlement may not be enough. A review of the Kiryandongo refugee settlement’s healthcare system reveals that any number of cases above zero should be considered unmanageable. The Kiryandongo refugee settlement has three primary healthcare facilities. The health centres that are available are understaffed and under-resourced. Makingvmatters more challenging, Professor Thumbi Ndung’u of the African Institute for Health Research says that, “[Africa doesn’t] have the hospitals, the CUs or the ventilators to deal with massive amounts of [infected] people.”[4] The COVID-19 pandemic has imposed unprecedented challenges on healthcare systems in developed nations, resulting in problems with staffing and resources. A system that is understaffed and under-resourced to begin with, such as in refugee settlements, is not well-positioned to meet the challenge of a highly infectious disease. Jane Ruth Aceng, Uganda’s minister of health, says the country is prepared to handle an outbreak in their refugee settlements. “We have tents that we have procured, and [which are] ready to be set up to manage people who may get infected wherever. For those who are severely ill, they will be referred and managed in the regional referral hospitals whose capacities are being built tohandle COVID-19.”[5] Uganda’s minister of health suggests that refugees with the virus will be properly quarantined. One would expect Uganda to be at the forefront of protecting refugees against COVID-19, as they have long protected refugees from other crises, such as the conflict in South Sudan. Uganda is known for its progressive refugee policies and allocating land plots to individual refugee families. Their generous policies have so far attracted 1.4 million refugees, mainly from neighbouring South Sudan and the Democratic Republic of Congo. Of the more than 800,000 South Sudanese refugees in Uganda, a reported 13,500 of them arrived between January 1 and March 24 2020. However, on March 25, the government made the decision to close its borders to new refugees.[7] In fairness, Uganda may only have been following the lead of the European Union.